2011
DOI: 10.1063/1.3627369
|View full text |Cite
|
Sign up to set email alerts
|

Superparamagnetic behavior in cobalt iron oxide nanotube arrays by atomic layer deposition

Abstract: Cobalt iron oxide nanotube arrays with various wall thicknesses were prepared by atomic layer deposition in porous anodic alumina template. Nanotubes uniform in thickness and homogeneous in composition can be obtained with aspect ratios on the order of 50. These nanotubes have a polycrystalline spinel structure. Both the mean grain size and the grain size distribution increase with the tube wall thickness. Correspondingly, their magnetic properties (remanence and coercive field) also have a strong dependence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“…Here, we used diethylzinc and H 2 O as the precursor pair at 150 °C for the deposition of a 100 nm ZnO layer into MACE-produced pores. This step is similar to the fabrication of nanotubes and nanowires using the template-based synthesis approach with ALD coatings. In our case, ideally all the pores with small diameters (<200 nm) can be completely filled, while those with large diameters (>200 nm) are partly filled, forming tubular structures. ZnO was used as the ALD filling material due to two important factors: (1) Si yields high selectivity with respect to ZnO when etched with a fluorine-based high-density plasma process (>400:1) and (2) ZnO is an electrically conductive metal oxide, which is very important for high-resolution SEM imaging (minimal charging when subjected to the e-beam).…”
Section: Resultsmentioning
confidence: 90%
“…Here, we used diethylzinc and H 2 O as the precursor pair at 150 °C for the deposition of a 100 nm ZnO layer into MACE-produced pores. This step is similar to the fabrication of nanotubes and nanowires using the template-based synthesis approach with ALD coatings. In our case, ideally all the pores with small diameters (<200 nm) can be completely filled, while those with large diameters (>200 nm) are partly filled, forming tubular structures. ZnO was used as the ALD filling material due to two important factors: (1) Si yields high selectivity with respect to ZnO when etched with a fluorine-based high-density plasma process (>400:1) and (2) ZnO is an electrically conductive metal oxide, which is very important for high-resolution SEM imaging (minimal charging when subjected to the e-beam).…”
Section: Resultsmentioning
confidence: 90%
“…The chemical precursor vapors are deposited by applying sequential pulses that form about one atomic layer each. Other metallic and oxide NTs with novel magnetic properties were synthesized by ALD and characterized (Figure 24.15d; Daub et al, 2007;Chong et al, 2011). This generates pinhole-free layers that are extremely uniform in thickness, suitable for coating nanostructures with complex geometry, including deep pores, trenches, and/or cavities .…”
Section: Atomic Layer Depositionmentioning
confidence: 99%
“…Ahmad et al (2011a) showed that the decrease of the thermal energy causes an increase in the coercivity and saturation magnetization of Co NTs. Superparamagnetic NTs of cobalt iron oxide also exhibit interesting properties at low temperatures, such as tunable blocking temperatures that were found to increase with increasing tube wall thicknesses (Chong et al, 2011). Superparamagnetic NTs of cobalt iron oxide also exhibit interesting properties at low temperatures, such as tunable blocking temperatures that were found to increase with increasing tube wall thicknesses (Chong et al, 2011).…”
Section: Temperature-dependent Magnetic Propertiesmentioning
confidence: 99%
“…Due to the quasi-periodic arrangement of the nanopore channels, narrow distribution of pore sizes, and interpore distances, relative ease to control the porous scales and self-ordering qualities by anodization conditions, excellent thermal stability, and very low-cost anodic porous alumina has been extensively used as templates for fabrication of various nanostructured materials such as nanodots [22][23][24], nanowires [25][26][27][28][29], nanotubes [30][31][32], and many other types [33][34][35], especially to realize the collective functioning of arrays of nanoelements which may not be realized by individual nanoelements [5,36], for applications in high-density magnetic media [37][38][39][40][41][42] [95,96]. For neutral electrolytes with pH in the range of 5-7, such as boric acid solution, ammonium borate, or tartrate aqueous solution, only barrier-type anodic alumina films with a uniform thickness will be formed by anodization [1,97].…”
mentioning
confidence: 99%